STRATEGI MANAJEMEN OPERASIONAL PONDOK PESANTREN ULUMUDDIN SUSUKAN CIREBON - Khulud Saadah Almadaniah; Jaharuddin Jaharuddin (Taksasila Edukasi Insani, 2023)
Islamic boarding schools have visionary and multidimensional orientations. In the era of globalization, Islamic education faces various demands and challenges that require specific management strategies to maintain the health of Islamic educational institutions. Moreover, the community has high expectations of Islamic boarding schools to provide Islamic responses and answers to contemporary challenges. The aim of this research is to describe the operational management of Ulumuddin Islamic Boarding School in Susukan Cirebon and to determine the implementation of management strategies there. This research employed a field study with a qualitative approach that described factual realities found through observation, interviews, and documentation. To analyze the data, the researcher grouped the themes and described them in the discussion. The results of the research indicate that operational management in Islamic boarding schools is not straightforward, but instead involves many related elements, which are described in detail in the discussion of this study.